A comparison of swimming skills in british and german children's books - Vogel, M.; Staub, I.; Kronenbürger, S.; Vogt, T. (XIVth International Symposium on Biomechanics and Medicine in Swimming Proceedings, 2023)
INTRODUCTION Previous research on British and German children`s books has shown that they may serve as transfer of knowledge to a society but might lead to a distorted representation of the importance of the competencies (i.e., submerging, and floating) [1]. To identify cultural differences or similarities in the learn-to-swim process, the competencies submerging and floating are compared by considering their frequency and implementation in the children`s books.